Hydrogen bonding in 2,6-bis(4-fluorophenyl)-3,5-dimethylpiperidin-4-one methanol solvate - Suresh, T.; Vijayakumar, V.; Kumar, L. Jyothish; Sarveswari, S.; Jotani, Mukesh M.; Otero-de-la-Roza, Alberto; Tan, Yee Seng *; Tiekink, Edward R. T. * (De Gruyter, 2016)
The crystal structure analysis of a 2,6-diaryl 4-piperidone derivative, isolated as a mono-methanol solvate, reveals that both the piperidone and the methanol molecule lie on a crystallographic mirror plane. A chair conformation is found for the piperidone ring with the aryl and methyl groups in equatorial positions. The most prominent feature of the molecular packing is the formation of supramolecular zigzag chains mediated by amine-N–H···O(methanol) and hydroxyl-O–H···N(amine) hydrogen bonds, i.e. the methanol molecule serves as a bridge between piperidone molecules. The molecular structure is compared with that determined in an unsolvated form and the gas-phase equilibrium structure, obtained using density-functional theory (DFT); differences relate, in the main, to the relative dispositions of the aryl rings. An analysis of the Hirshfeld surfaces of the experimental structures indicates very similar relative contributions with the notable exception being the contribution by O···H/H···O which at 13.7% in the methanol solvate is >8.5% in the unsolvated form.